Implementasi Kepemimpinan Yesus Kristus Menurut Yohanes 13:1-20 - Hotman Parulian Simanjuntak (Sekolah Tinggi Teologi Yerusalem Baru, Manado, 2020)
AbstractLeadership is an integral part of all human civilization because everyone needs a leader. Leader and leadership cannot be separated from one another. Where the purpose of choosing a leader is to influence, admonish, direct the people they lead to the goals they want to achieve. Thus, leadership is more likely to function and not position. The world offers and shapes leaders who are more focused on position and authority. This clearly contradicts the leadership of Jesus Christ in John 13: 1-20. It happens in Christian leadership today. Some of the Christian leaders have not been able to be examples of holiness in life, where they are not willing and able to leave old habits. Sometimes some of the Christian leaders live in enmity, either with the congregation, council or with fellow Christian leaders. Based on the above problems, the author will examine more deeply referring to the title: